ANALISIS RESPON CALON GURU TERHADAP PENGGUNAAN GEOGEBRA SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA - Asnawi, Muhammad Hasan; Ulum, Moh. Miftakhul; Qohar, Moh. Abdul; Juliantoro, Muhammad Arif (International Conference on Humanity Education and Society (ICHES), 2024)
Abstract Efforts to improve the quality of mathematics learning certainly need to involve and prepare students as prospective mathematics teachers. In addition to competent mastery of material, prospective teacher students must be equipped with the ability to provide interactive mathematics learning between teachers and students through technological advances. The aim of this research is to analyze the responses of prospective mathematics teachers to the use of GeoGebra as a mathematics learning medium. This research uses descriptive quantitative methods. The subjects of this research were prospective teacher students taking the Introduction to Computer Science course. Of the 20 prospective teacher students who were given a questionnaire, 3 were then randomly selected for in-depth interviews. The research results show that more than 95% of prospective teacher students realize that GeoGebra can be a solution or tool in visualizing mathematical concepts. Starting from basic mathematics concepts to upper intermediate level can be visualized with GeoGebra. So that students will more easily understand mathematical concepts and can improve the mathematics learning process through interactive media assisted by GeoGebra.